Initial effects of Mental Health First Aid training on mental health literacy, social distance, stigma, mental health, and quality of life in the German adult population$tfindings from a pilot study - Schick, Anita; Henn, Cirus; Send, Tabea; Maltese, Simona; Deuschle, Michael; Reininghaus, Ulrich (European psychiatry, 2025)
BackgroundDespite the high prevalence of mental disorders, knowledge about mental health, its promotion, prevention, and pathways to care in the general population remain limited. Mental Health First Aid (MHFA) seeks to increase mental health literacy in the general population and enable individuals to support others with mental health problems until professional help is available. This study aimed to investigate the feasibility and initial effects of MHFA training on (i) mental health literacy, (ii) stigmatizing attitudes toward individuals with mental health problems, (iii) social distance, (iv) trainees’ mental health, and (v) quality of life.MethodsIn an uncontrolled pilot study, individuals aged 18-75 years who participated in MHFA courses in Germany were recruited. Outcomes were assessed at baseline, post-training, and 6-month follow-up.ResultsIn total, 362 participants (mean age 43 years, 78% female) enrolled in the study at baseline. Retention was about 50% for post-training and 60% for follow-up assessment. At post-training, mental health literacy was increased (adjΒ = 6.77, 95% CI = 5.69 to 7.84) and social distance (adjΒ = −2.30, 95% CI = −2.73 to −1.87) and stigmatizing attitudes (adjΒ = −2.61, 95% CI = −3.25 to −1.97) were reduced. These effects were also evident at 6-month follow-up. There were no effects on trainees’ mental health. At the 6-month follow-up, 89% of trainees had talked to someone with mental health problems at least once, and 65% of trainees were quite or very confident in offering help.ConclusionsOur findings suggest initial beneficial effects of MHFA training as implemented in Germany. A randomized controlled trial of MHFA in Germany is now warranted.